Real-World Outcomes in Patients with Advanced Penile Squamous Cell Carcinoma Receiving Immune Checkpoint Inhibitors: A Single Institution Experience - Tony Z. Zhuang; Subir Goyal; Katherine B. Case; T. Anders Olsen; Shalini Vemuru; Ahmet Yildirim; Rohit V. Goswamy; Jacqueline T. Brown; Bradley C. Carthon; Omer Kucuk; Mehmet Asim Bilen; Viraj A. Master; et al. (Journal of Immunotherapy and Precision Oncology)
Introduction Advanced penile squamous cell carcinoma (pSCC) is a rare and aggressive malignancy with a poor prognosis and an unmet need for biomarkers. We performed a retrospective evaluation of real-world efficacy, safety outcomes, and baseline inflammatory biomarkers in patients with advanced pSCC treated with immune checkpoint inhibitors (ICIs). Methods We performed a retrospective review of patients with advanced pSCC who received ICIs from 2012 to 2023 at the Winship Cancer Institute of Emory University in Atlanta, GA. Demographics, disease characteristics, and optimal cutoffs of baseline biomarkers obtained before ICI initiation were described. Human papillomavirus (HPV)/p16+ status was determined by immunohistochemistry. Programmed death-ligand 1 (PD-L1) positivity was defined as >1%. Immune-related adverse events (irAEs) were graded per Common Terminology Criteria for Adverse Events criteria and captured through clinical documentation. Clinical benefit was defined as complete response, partial response, or stable disease based on Response Evaluation Criteria in Solid Tumors (RECIST) 1.1. Overall survival (OS) and progression-free survival (PFS) were assessed by Kaplan-Meier method and univariate Cox regression (UVA) using a significance level set at p < 0.05. Neutrophil-to-lymphocyte (NLR), monocyte-to-lymphocyte (MLR), platelet-to-lymphocyte (PLR), and neutrophil-to-eosinophil ratios (NER) were collected from complete blood count data. Results Twenty-one patients were included of whom 71.4% were White and 28.6% were Black. Median age at ICI initiation was 56 years (38–76 years). Most patients had Eastern Cooperative Oncology Group performance status ≥2 (61.9%). At diagnosis, 4.8%, 33.3%, and 61.9% were stage 2, 3, and 4, respectively, of whom eight patients had initial distal metastases. Of patients with available data, 7 of 11 patients (63.6%) were PD-L1+ and 8 of 9 (89%) patients were HPV+. Median follow-up was 8.4 months and median time to ICI treatment from diagnosis was 15.6 months. ICI was first line (1L) in 1 patient (4.8%), 2L in 13 (61.9%), 3L in 6 (28.6%), and 4L in 1 (4.8%). Five patients achieved clinical benefit of whom three had partial response and two had stable disease. Median OS was 8.2 months (95% CI, 2.3–15.7) and PFS was 1.9 months (95% CI, 1.3–3.2). Notably, three patients with PD-L1 positivity, microsatellite instability (MSI)-high, or high tumor mutational burden (TMB) demonstrated response to ICI. Higher baseline NLR (hazard ratio, 10.0; 95% CI, 2.73–54.2) at optimal cutoff was associated with shorter OS and PFS on UVA. Three patients (14.3%) developed grade 3/4 ICI-related adverse events. Conclusions Our real-world analysis summarizes our institutional experience and provides granular clinical and molecular attributes of patients with therapeutic response, which may aid in patient stratification within ICI-based clinical trials. Overall, we confirm poor response rates of pSCC to ICI in an unselected approach, consistent with multicenter studies. ICIs may be effective and tolerable therapy in a subset of patients. NLR may be a potential biomarker to assess ICI response in pSCC.